A pilot study of the bedside tests for aspiration in acute stroke. - Biem, Henry Jay. (University of Ottawa (Canada), 1998)
The aim of this thesis was to provide feasibility and statistical information that could be used to develop a grant proposal for a multidisciplinary study of the reliability and accuracy of the bedside diagnosis of aspiration and dysphagia in acute stroke patients. The objectives of this pilot study were: (1) To determine the feasibility of doing simple bedside tests for dysphagia and aspiration and determining intra-observer and inter-observer reliability. (2) To determine the required sample sizes to measure the inter-observer reliability of each of the video-recorded bedside tests with the Kappa statistic within a desired confidence interval based on estimates of the observed and expected agreements. (3) To determine the rate of admission of acute stroke patients at one hospital center and the approximate proportion of acute stroke patients who are eligible for enrollment and give consent. (4) To determine the approximate proportion of recruited acute stroke patients with the clinical outcomes of pneumonia and disruption of oral feeding. The pilot study used a prospective design to determine the agreement between two blinded observers for each of the various bedside tests recorded on videotape. It was conducted at Etobicoke General, a suburban community hospital. (Abstract shortened by UMI.)
Keywords: Health Sciences, Medicine and Surgery.